APPROPRIATE TREATMENT FOR INSECURE STUDENTS IN INCREASING ENGLISH SPEAKING SKILLS; MENTAL HEALTH SUPPORT AT SCHOOL - Merryanti, Eva; Sutapa, Yohannes Gatot; Regina, Regina (Jurnal Review Pendidikan dan Pengajaran, 2024)
Mental well-being at school is a strategic issue and has concerned education practitioners lately. Most teachers know the importance of mental health and its impact on student’s learning achievement especially in increasing the speaking skill of students. In English class, students with mental well-being tend to have higher self-confidence in the learning process, especially in speaking activities while some students with insecurity experience failure. This is the reason for researchers to research these students. The case study that occurred at primary school, became a problem faced by teachers in English learning. Most students with insecurity observed in this research are great students but they lose self-confidence so they fail in learning process. This research aims to describe this phenomenon in detail by collecting data through observation and interviews. Teachers apply several treatments to make students confident so they dare to speak English in the learning process. Before applying the appropriate treatment teachers should enrich their knowledge and insights regarding student psychology to be more sensitive and care for students with mental conditions. By knowing the condition of students, the teacher can consider what actions can help and support them to be motivated to learn. The description of causes, how the symptoms of insecure students, and what should teachers do with insecure students. The results of this research are that the student’s self-confidence students have increased and then the teacher finds the progress of insecure students in their learning achievement.